2013
DOI: 10.1590/s0100-736x2013000600004
|View full text |Cite
|
Sign up to set email alerts
|

Serial superficial digital flexor tendon biopsies for diagnosing and monitoring collagenase-induced tendonitis in horses

Abstract: Pesq. Vet. Bras. 33(6):710-718, junho 2013 710 RESUMO.-[Biópsias seriadas do tendão flexor digital superficial para o diagnóstico e monitoração da tendinite induzida por colagenase em equinos.] Objetivou-se demonstrar a viabilidade de uma técnica de biópsia na realização de avaliações sequenciais de amostras de tecido do tendão flexor digital superficial (TFDS) do membro toráci-co, em equinos hígidos e em equinos submetidos à indução de tendinite do TFDS. Oito equinos adultos foram avaliados em duas fases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…About 43-93% of affected horses sustaining re-injury and get early retirement and only about 20-60% of the affected horses were returned successfully to racing after long period of layoff and rehabilitation lasts from 6 up to 18 months (Zuffova et al, 2013). Ultrasonography is one of the most accurate, well-tolerated and non-invasive tools to evaluate the tendon structure after an injury, follow-up the healing process, and establish prognosis (Crevier-Denoix et al, 2005 andLacerda-Neto et al, 2013). Rural and Maria (2010) concluded that the assessment of the core lesion cross section area at MIZ, the echogenicity of the core lesion and the fiber alignment of the core lesion were considered the main ultrasonographic diagnostic criteria of the severity of the injured tendon.…”
Section: Introductionmentioning
confidence: 99%
“…About 43-93% of affected horses sustaining re-injury and get early retirement and only about 20-60% of the affected horses were returned successfully to racing after long period of layoff and rehabilitation lasts from 6 up to 18 months (Zuffova et al, 2013). Ultrasonography is one of the most accurate, well-tolerated and non-invasive tools to evaluate the tendon structure after an injury, follow-up the healing process, and establish prognosis (Crevier-Denoix et al, 2005 andLacerda-Neto et al, 2013). Rural and Maria (2010) concluded that the assessment of the core lesion cross section area at MIZ, the echogenicity of the core lesion and the fiber alignment of the core lesion were considered the main ultrasonographic diagnostic criteria of the severity of the injured tendon.…”
Section: Introductionmentioning
confidence: 99%